Omesso versamento IVA e crisi d’impresa: tra rigorismo giurisprudenziale e necessità di riformulazione legislativa - Bizzarri, Ramona (Cultura giuridica e diritto vivente, 2017)
Failure to pay VAT and business crisis: case-law stringency and need for legislative amendments] Article 10 ter of Legislative Decree No 74/2000 punishes any person who fails to pay the value added tax by the deadline, regardless of the intent to evade. The Supreme Court adopted a strict interpretation, that doesn’t give many chances of impunity to who fails to pay VAT because of business crisis. The paper highlights the imperfections of the case-law rigor and underlines the necessity of a legislative reform that changes the subjective element of this tax crime.